Manajemen Kolam Renang se-Kecamatan Boja Kabupaten Kendal Tahun 2020 - ashari, triawan; Mulyono, Aris (Universitas Negeri Semarang, 2023)
The purpose of the study was to determine the management of swimming pools in the Boja District, Kendal Regency. The research method used is qualitative research, namely collecting data through observation, interviews, and documentation. The research location was carried out in four swimming pools in Boja District, namely the Boja Swimming Pool, the Boja River Walk Swimming Pool, the Tirta Nusantara Swimming Pool and the Trisobo Park Agro Tourism Swimming Pool. The results obtained in the form of data planning (planning), Organizing (Organizing), Staffing (Staffing), Motivating (Motivating), Supervision (Controlling). Based on the existing data, it can be concluded that the management of swimming pools in the Boja District in 2020 is said to be good, but the supervisory management function has not gone well. The results of this research are expected that the owners of swimming pools in Boja District will increase supervision so that the swimming pool can run well and make innovations to improve the quality of the swimming pool.